2020
DOI: 10.3390/cancers12061561
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Lung Fibrosis: Preclinical Animal Models and Therapeutic Strategies

Abstract: Radiation-induced lung injury (RILI), including acute radiation pneumonitis and chronic radiation-induced lung fibrosis, is the most common side effect of radiation therapy. RILI is a complicated process that causes the accumulation, proliferation, and differentiation of fibroblasts and, finally, results in excessive extracellular matrix deposition. Currently, there are no approved treatment options for patients with radiation-induced pulmonary fibrosis (RIPF) partly due to the absence of effective targets. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 99 publications
0
76
0
Order By: Relevance
“…Mainstream researches show that the mechanism of RILI may be because ionizing radiation can directly cause DNA damage and a large number of free radicals in lung tissue cells, which can mediate and amplify the damage of alveolar epithelial cells and vascular endothelial cells by promoting oxidative stress, vascular damage and inflammatory response, further leading to RILI [56][57][58]. Nowadays there is no specific therapeutic drug for radiation-induced lung injury, only glucocorticoids are used in the treatment of RILI, but it's not specific treatment [10]. Therefore, there is an urgent need to find a strategy to prevent or treat RILI in clinic.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Mainstream researches show that the mechanism of RILI may be because ionizing radiation can directly cause DNA damage and a large number of free radicals in lung tissue cells, which can mediate and amplify the damage of alveolar epithelial cells and vascular endothelial cells by promoting oxidative stress, vascular damage and inflammatory response, further leading to RILI [56][57][58]. Nowadays there is no specific therapeutic drug for radiation-induced lung injury, only glucocorticoids are used in the treatment of RILI, but it's not specific treatment [10]. Therefore, there is an urgent need to find a strategy to prevent or treat RILI in clinic.…”
Section: Perspectivementioning
confidence: 99%
“…At present, the main mechanism of RILI is still unclear, and there is no clinically effective drug for it. Nowadays the clinical treatment of RILI is mainly based on the use of glucocorticoids, combined with symptomatic treatment such as antibiotics, relieving cough, reducing phlegm and relieving asthma drugs, but none of them are specific treatment [ 8 10 ]. Therefore, it is urgent to explore the mechanism of RILI and find effective therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggested that inhalation of silica and asbestos particles in rats results in fibrotic nodule formation which closely mimics prominent features of silicosis and asbestosis in humans with long-term occupational exposure (184,185). Additionally, whole thorax irradiation in mice has been invaluable to study early inflammatory responses in radiation-induced lung fibrosis (186). It is well-established that IPF includes genetic predisposition affecting genes encoding e.g., surfactant protein-C (SP-C) (187), SP-A (188), Mucin-5B (MUC5B) (189), telomerase reverse transcriptase (TERT), and telomerase RNA component (TERC) (145).…”
Section: In Vivo and In Vitro Models Of Pulmonary Fibrosismentioning
confidence: 99%
“…Pulmonary fibrosis (PF) is a chronic lung disease, and its incidence has been rising in recent years ( Wu and Xu, 2020 ; Li et al, 2021 ). PF usually affects elderly patients, and radiation and mechanical or chemical stimulation have become the main risk factors associated with PF ( Froidure et al, 2020 ; Jin et al, 2020 ; Yang et al, 2020 ). The main pathological features of PF are alveolar epithelial cell damage, fibroblast proliferation and activation, excessive collagen deposition, and a large accumulation of extracellular matrix ( Sauler et al, 2019 ; Zhi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%